Origins of modern language teacher education: The influence of related disciplines on the educational breakthrough of the 1990s. Bridging past and future - Komorowska, Hanna (Neofilolog, 2022)
The article aims at identifying the roots of the dramatic changes which took place in the philosophy, curricula and methods of pre- and in-service teacher education in the early 1990s. Integration of teacher training programmes with university education, balanced introduction of theory and field experience, skills- and competence-based professional development of language teachers based on the concept of the reflective practitioner, trainee-centred teaching methodology, i.e. innovative solutions marking the breakthrough in language teacher education of the last decade of the 20th century were the result of advancements in the educational sciences, sociology, anthropology, psychology and philosophy. The main directions of influence exerted by each of these disciplines on teacher training programmes in the United States, Great Britain and countries of Central and Eastern Europe are discussed with special emphasis on developments which shape the language policy of the main European institutions at present and which are likely to continue exerting an impact in the near future.